Occurrence of Pacific bluefin tuna Thunnus orientalis larvae off the Pacific coast of Tohoku area, northeastern Japan: Possibility of the discovery of the third spawning ground. (14th October 2019) - Tanaka, Yosuke; Tawa, Atsushi; Ishihara, Taiki; Sawai, Etsuro; Nakae, Misato; Masujima, Masachika; Kodama, Taketoshi
Abstract: Recently, based on the histological studies it is suggested that Pacific bluefin tuna (PBF) spawns in the Kuroshio–Oyashio transition, off the Pacific coast of northeastern Japan, in addition to the previously identified two spawning areas of the northwestern Pacific around the Nansei Islands and the Sea of Japan. Distributional surveys for PBF larvae have not been conducted in the Kuroshio–Oyashio transition, and thus, we conducted PBF larval surveys at twenty stations in this area in early August 2018 to obtain evidence for the spawning of PBF. Twelve PBF larvae (3.9–7.2 mm in body length) were collected at six stations where sea surface temperature ranged from 27.2 to 28.2°C. Otolith microstructure analysis indicated that age of these larvae ranged from 4 to 11 days after hatching and the larvae hatched in late July. Growth of the collected larvae was comparable to those in the other two spawning grounds. Therefore, PBF spawns, hatches, and at least survives to the postflexion stage, 11 days after hatching in the Kuroshio–Oyashio transition. This fact potentially has a large impact on recruitment processes of PBF if they survive to recruitment in this third spawning ground.